Consumer Shopping Behaviour in the New Era of Retailing: An Empirical Study on Food and Grocery and Apparel Purchase in East India - Chattopadhyay, Ayan (Indian Journal of Marketing, 2013)
Retailing in India has witnessed a sea change, not only in terms of emergence of newer formats, but also in terms of the behaviour of the shoppers. Indian shoppers who had limited choices till a decade back are now exposed to a plethora of choices, which indicates a radical shift from a conservative mind set to a spending mind set. The present research study aims to understand and analyze the ever changing consumer behavioural patterns while shopping. The study involves comparing how the consumer characteristics vary while shopping food and grocery items and apparel in four state capitals of West Bengal, Bihar, Orissa, and Jharkhand. The study covers a sample base spread across the four cities of Kolkata, Ranchi, Patna, and Bhubaneswar. Primary research forms the basis of this study. The data analysis as detailed in the research study turned up some predictable as well as surprising results. The paper concludes that for food and grocery purchase, location (nearness to home) was the prime consideration for the respondents of Kolkata and Bhubaneswar, while it was range for both - respondents from Patna and Ranchi. Ambience was the least important parameter for the respondent populations from the 4 state capitals. For apparel purchase, range or assortment was the most important parameter for the respondent populations from the 4 state capitals. The behavioural pattern of the respondents with respect to frequency of visit, preferred group size during shopping, and decision maker in choosing a shopping destination revealed a fairly uniform pattern across the state capital locations.